The life and contributions of Syed Sheikh al-Hadi to the educational reforms in Malaya - Zakariya, Hafiz; Akgun, Tayfun (Universiti Malaysia Terengganu Press, 2022)
This chapter presents a brief biography and contributions of al-Hadi to Islamic reformism in Malaya especially in the realm of education.